First-principles and CALPHAD-type study of the Ir-Mo and Ir-W systems - Huang Y.-Y.; Wu B.; Li F.; Chen L.-L.; Deng Z.-X.; Chang K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This study presents the thermodynamic modeling of the Ir-Mo and Ir-W systems by means of the CALPHAD (CALculation of PHAse Diagrams) approach supported with the first-principles calculations. A critical evaluation of the phase equilibria and the thermodynamic property data in literature was conducted for both systems. Due to the lack of experimental data, the first-principles calculations were applied to obtain the enthalpies of the solid and intermetallic phases. The thermodynamic parameters were assessed using the PARROT module of Thermo-Calc. A set of self-consistent parameters for the Ir-Mo and Ir-W systems was obtained after the optimization. Satisfactory agreement between the calculated results and the experimental data, including phase equilibria and thermodynamic properties was achieved.